A MARGINALIZAÇÃO DA LITERATURA MARANHENSE NO ENSINO MÉDIO: dimensões curriculares - Martins, Ana Patrícia Sá (2011)
The research aims to study the teaching of Literature at Liceu Maranhense, and as training, reading habits and builders agents of curriculum are factors that influence teaching practice. Throughout this paper, we draw a brief overview about the teaching of literature and how it was and is being discussed in official documents dealing with the teaching of language and literature in High School. We also did an analysis of the historiographical of Maranhense literature, since we believe that the understanding of how it was throughout history, has given us an understanding of their place in the literary and historical in Maranhão. As an analysis of historical overview of Liceu Maranhense and its place in the public education of Maranhão, since its foundation in the mid-nineteenth century, we also described analytically as it is currently structured administratively and pedagogically. All this, to finally look at the teachers' responses collected through questionnaires and supplemented with observations made during their meetings and educational classes that we might realize the conceptions of literature, who know the literature of Maranhão, teaching Literature in their higher education and their teaching practices as teachers of literature, which also analyzed the agents that influence the construction of the curriculum curriculum of Portuguese Language and Literature. To achieve these steps, we have the theoretical contributions of Discourse Analysis French line, taking the notion of discourse from Foucault (2007), as well as Bakhtin's dialogism and polyphony (1992). To help us in analysis of the teaching of literature we have Zilberman (1990), (1988), (2004), Antônio Cândido (1972), (1975), (2000), Lajolo (1982) among others. Agents on the builders of the curriculum and teacher training of teachers in the course of literature, have shaped the Apple (1982), Chiappini (2002), Forquin (1992), Candide (1995), Oliveira (2008), Silva (2006), Paulino (1998), Pacheco ( 2003), May (1998) and Bourdieu (1998), (2003), (2006) among others. Our study allowed us to conclude that the superficial training that teachers of Portuguese Language and Literature have acquired the courses of Letters is a leading factor for the marginalization of the teaching of Maranhense literature, as well as the devaluation of the instructions for entrance examinations, pointed as the main agent in the construction of language and literature curriculum. Given the above, it is necessary an urgent change in the course programs of letters, as in the parallel courses of teacher training, emphasizing the need for recovery and rescue of our literary and historical identity.